Sliding Simulation of Automotive Brake Primary Contact with Variable Amounts of Copper and Graphite Nanoparticles; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Dmitriev A. I. Andrey Ivanovich (2016, 2016)
Title screen